Production of Arbuscular Mycorrhizal Fungi Inoculum at Various Cow Urine POC Concentrations Using Sorghum (Sorghum bicolor L. Moench) Host in Hydroponic System - Arbi Abdillah; Oetami Dwi Hajoeningtijas; Agus Mulyadi Purnawanto (Journal of Tropical Mycorrhiza, 2026)
This study aimed to evaluate the production of arbuscular mycorrhizal fungi (AMF) inoculum at various concentrations of cattle urine-based liquid organic fertilizer (LOF) using sorghum (Sorghum bicolor L. Moench) as the host plant in a hydroponic system. The experiment was conducted using a Completely Randomized Design (CRD) with five treatments: PO (control), P1 (100% AB Mix), P2 (25 mL L-1 cattle urine LOF), P3 (50 mL L-1 cattle urine LOF), and P4 (75 mL L-1 cattle urine LOF). The observed parameters included the percentage of root colonization, spore density per 10 g of substrate, and host plant growth, as indicated by plant height and biomass. The results demonstrated that cattle urine concentration had a significant effect on the success of AMF symbiosis and spore production. Treatments PO (control without nutrient addition) and P2 (25 mL L-1 cattle urine LOF) produced the most effective outcomes, as indicated by the highest spore density and root colonization percentage compared to the other treatments. These findings suggest that low-nutrient conditions or low concentrations of cattle urine create an optimal environment for AMF proliferation. In conclusion, hydroponic production of AMF inoculum under minimal nutrient input or low doses of cattle urine represents an effective method for producing high-quality biofertilizer.